432 Brain Structure and Baroreflex Sensitivity Associations in Obstructive Sleep Apnea with and without CPAP. (3rd May 2021) - Pal, Amrita; Martinez, Fernando; Aysola, Ravi; Harper, Ronald; Henderson, Luke; Macey, Paul
Abstract: Introduction: Obstructive sleep apnea (OSA) disrupts multiple aspects of autonomic regulation; it is unclear whether intervention with continuous positive airway pressure (CPAP) can correct such disruptions. One key index of autonomic regulation is baroreflex sensitivity (BRS), an index that indicates heart rate (HR) changes to blood pressure (BP) alterations, and which is a significant measure for evaluating long-term cardiovascular changes induced by OSA. BRS can be assessed from BP and HR changes during an autonomic challenge task such as handgrip (HG). In a cross-sectional study, we assessed BRS during HG in untreated OSA (OSA_un) and CPAP treated OSA (CPAP), together with healthy control (CON) participants to determine if CPAP can recover BRS. Methods: We collected ECG and continuous beat-by-beat BP from 95 people: 32 newly-diagnosed OSA_un (51.5±13.9years; AHI 21.0±15.3events/hour; 20male); 31 CPAP (49.4±14.0years; 22.4±14.1events/hour in initial diagnosis; 23male); and 32 CON (44.1±13.8years; 10male). We acquired data over 7 mins, during which people performed three 30s HGs (60 s baseline, 90 s recovery, 80% maximum strength). We calculated BRS over the 7 min period using sequence analysis in AcqKnowledge 5.0 BRS, followed by group comparisons using ANOVA. We also analyzed BP, HR, and their variabilities: BPV and HRV (sympathetic-vagal). Results: Mean arterial BP increases during HG were similar in all groups, although baseline mean arterial BP was higher in OSA_unc and CPAP, relative to CON (p < 0.05; OSA_un:mean±std, 90±11mmHg; CPAP: 88±10mmHg; CON 82±13mmHg). BRS was lower in OSA_un and CPAP, relative to CON (p < 0.05; OSA_un: 13.1±7.6 ms/mmHg; CPAP: 13.7±9.0 ms/mmHg; control 18.3±11.9 ms/mmHg). Other cardiovascular measures of BPV, HR, and HRV in addition to BP showed significant increases in response to HG, but these changes were similar in all 3 groups. Conclusion: BRS during HG was reduced in both OSA_un and CPAP compared to CON, while HG evoked similar overall changes in BP and HR in all three groups. Although CPAP reduces sympathetic tone measured as Muscle Sympathetic Nerve Activity (MSNA), BRS appears to be unaffected by the intervention. Irreversible changes in the baroreflex network may occur with OSA that are not altered with CPAP usage. Support (if any): NR-017435, HL135562